2022
DOI: 10.1039/d2ta02223k
|View full text |Cite
|
Sign up to set email alerts
|

Organic electrolyte design for practical potassium-ion batteries

Abstract: Potassium-ion batteries (PIBs) are promising as a low-cost and complementary technology to lithium-ion batteries (LIBs) because of the relative abundance of potassium. Electrolyte is a critical component and governs the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…The irreversible capacity loss can be attributed to the irreversible decomposition of electrolyte to form solid electrolyte interphase (SEI) films. 35–38 As exhibited in Fig. 3c, the SeNCRs retain a reversible capacity of 303.5 mA h g −1 after 100 cycles, which is higher than those of the CRs (199.8 mA h g −1 ) and the SeCRs (215.8 mA h g −1 ).…”
Section: Resultsmentioning
confidence: 87%
“…The irreversible capacity loss can be attributed to the irreversible decomposition of electrolyte to form solid electrolyte interphase (SEI) films. 35–38 As exhibited in Fig. 3c, the SeNCRs retain a reversible capacity of 303.5 mA h g −1 after 100 cycles, which is higher than those of the CRs (199.8 mA h g −1 ) and the SeCRs (215.8 mA h g −1 ).…”
Section: Resultsmentioning
confidence: 87%
“…Besides, the high performance of PIBs benefit from suitable electrodes size, reliable mechanical properties as well as stable solid-electrolyte interphase (SEI) layer, in which stable SEI might alleviate electrolyte disintegration and buffer the large volume variations during long cycle. [31][32][33] Moreover, previous studies have proved that using the incorrect size of electrode materials results in a huge capacity loss during cycling. 34 Hence, it is an urgent requirement and a challenging proposition to search for practicable PIB anode materials of the correct size that can facilitate the diffusion of K + and provide an exceptionally stable structure for buffering volume change.…”
Section: Introductionmentioning
confidence: 99%
“…Developing suitable electrode materials capable of accommodating significant volume variations during the insertion or extraction of K + ions remains challenging owing to their relatively large ionic radius (the ionic radius of K + , Na + , and Li + ions are 1.38, 1.02, and 0.76 Å, respectively). Besides, the high performance of PIBs benefit from suitable electrodes size, reliable mechanical properties as well as stable solid‐electrolyte interphase (SEI) layer, in which stable SEI might alleviate electrolyte disintegration and buffer the large volume variations during long cycle 31–33 . Moreover, previous studies have proved that using the incorrect size of electrode materials results in a huge capacity loss during cycling 34 .…”
Section: Introductionmentioning
confidence: 99%
“…35 Various strategies, such as nanostructure engineering, alloying with other metals, hybridization with carbon materials, and electrolyte optimization, have been recently applied to improve the electrochemical performance of Bi anodes. [35][36][37][38][39][40][41] For example, Li's group demonstrated that the cycling stability of commercial Bi was improved by replacing the conventional ester-based electrolyte with an ether-based electrolyte. 17 Qiao et al synthesized a carbon-coated double-shell nanostructured Bi box, demonstrating a reversible capacity of over 200 mA h g À1 aer 200 cycles.…”
Section: Introductionmentioning
confidence: 99%